Effect of the Frictional Properties of Sunflower Seeds on the Efficiency of Pressing Equipment - Berezin M.; Borisov V. (Техника и технология пищевых производств)
Introduction. The process of oil extraction from oilseeds is very complicated as it depends on a large number of related factors. The complex porous structure of pulp is a combination of three phases: dry solids, liquid (oil), and air. Therefore, the study of the process of pulp pressing requires a special method for determining the friction characteristics of the material. Study objects and methods. To determine the friction and volume characteristics of oilseeds, an original experimental unit was developed and manufactured. The study involved samples of the same mass weighted using a high-accuracy analytic balance (permissible error = ± 5%). The first stage of the experiment featured volume characteristics of ten samples. The second stage featured friction characteristics of the five first samples obtained during the first stage at different pressures. Results and discussion. The pressure time proved to have a more significant effect on the oil yield than the pressure volume, since the complex capillary structure of the pulp demonstrated a significant hydrodynamic resistance to oil outflow. The dependence of the oil yield on the pressure was described by an asymptotic function; the limit (asymptotic) value of the pressure was 48 MPa. At this pressure, the oil yield reached φ = 54 %. The dependence of the friction coefficient on the values of temperature, pressure, and sliding velocity was described by a power-law regression equation with the coefficient of accuracy of approximation R2 = 0.96. Conclusion. The obtained data are of practical importance and can be used to improve the efficiency of pressing equipment.